2016
DOI: 10.1017/s0033291716002294
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic stress disorder and cardiometabolic disease: improving causal inference to inform practice

Abstract: Posttraumatic stress disorder (PTSD) has been declared “a life sentence” based on evidence that the disorder leads to a host of physical health problems. Some of the strongest empirical research—in terms of methodology and findings—has shown that PTSD predicts higher risk of cardiometabolic diseases, specifically cardiovascular disease (CVD) and type 2 diabetes (T2D). Despite mounting evidence, PTSD is not currently acknowledged as a risk factor by cardiovascular or endocrinological medicine. This view is unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 128 publications
6
103
1
2
Order By: Relevance
“…Sixth, for the sake of parsimony, we did not include information on medical conditions like hypertension that might be on the pathway from PTSD to CVD risk biomarkers or occur simultaneously with these elevated biomarker values. However, these conditions are unlikely to be confounders because they are unlikely to cause PTSD(2). Seventh, we note that, overall, biomarker change over the 10–16-year period was modest.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, for the sake of parsimony, we did not include information on medical conditions like hypertension that might be on the pathway from PTSD to CVD risk biomarkers or occur simultaneously with these elevated biomarker values. However, these conditions are unlikely to be confounders because they are unlikely to cause PTSD(2). Seventh, we note that, overall, biomarker change over the 10–16-year period was modest.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigators have examined posttraumatic stress disorder in relation to a range of health outcomes (including rheumatoid arthritis, stroke, heart disease, and cancer), some of the strongest empirical research, in terms of methodology and findings, has been with cardiometabolic diseases. 70,71 Numerous methodologically rigorous prospective population-based observational studies have found that posttraumatic stress disorder is associated with increased risk of incident CVD [72][73][74][75][76][77][78][79][80][81][82][83][84] and T2DM. [85][86][87] However, whether and how much of the relation between childhood adversity and cardiometabolic disease may be explained by posttraumatic stress disorder is unclear, especially because these studies have included traumatic events over the life course, with a substantial proportion of studies focused on veterans and military service-related trauma, not just adversity during childhood.…”
Section: Mental Health Factorsmentioning
confidence: 99%
“…This includes heart disease and heart failure [2023], hypertension [24], stroke and/or myocardial infarction [25, 26], and chronic obstructive pulmonary disease [27]. Based on these associations, we [4] and others [28] have suggested that it may be appropriate to consider PTSD as a risk factor when deciding which patients require early screening for cardiometabolic pathology.…”
Section: Traumatic Stress and Premature Metabolic And Cardiovascular mentioning
confidence: 99%